THE ENHANCEMENTS SKILL OF WRITING POETRY BY DWA (DIRECTED WRITING ACTIVITY) STRATEGY - Galuh Lukitasari; Siti Wahyuningsih; Tri Budiharto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this research was to improve the skill of writing poetry by applied DWA (Direct Writing Activity) Strategy for fifth grade students in SDN Munggung 1 Surakarta on academic year of 2018/2019.The form of this research was a Classroom Action Research which conducted in two cycles. Each cycle consisted of four stages i.e. planning, action, observation, and reflection. The subjects of this research included teacher and 33 fifth grade students in SDN Munggung 1 Surakarta. The data collected by interview, observation, test, and documentation techniques. The data validity test were using content validity, triangulation of resource, and triangulation of technique.The result of this research shows the improvement of skill of writing poetry values from pre-action, cycle I until cycle II.